Spaces for planning evolution. Path, inter and goal dependencies in the revival of spatial planning in Argentina - Alves Rolo, Rodrigo Hernán (Wageningen University, 2025)
Tesis presentada para optar al título de Doctor en Filosofía, de la Universidad de Wageningen, en octubre 2022